Membranes enhanced anti-biofouling properties by chitosan and chitosan-powder activated carbon composite / Hasan Fouzi Salem Gafri - Hasan Fouzi , Salem Gafri (2019)
Understanding the adhesion of microorganisms to biotic surfaces is an important consideration in many industries. Bacterial adhesion to surfaces is related to biofilm cells are at least 500 times more resistant to antibacterial agents compared to planktonic cells. Membrane technologies have been set up as a convincing and financially alluring choice for separation and purification processes in the water treatment. Membrane fouling leads to diminishing the membrane performance, serious deficient production, and excessive operational prices. Rivers and lakes are primary sources of water for towns and villages. However, the water bodies’ quality is currently deteriorating due to urbanization and other anthropogenic activities. The first aim of this research was to understand the physiochemical and biological characteristics of water samples conducted within July 2016 to April 2017 at designated eight points from Pantai River, Anak Air Batu River, and Varsity Lake, University of Malaya, Kuala Lumpur, Malaysia. The results were compared with the Water quality index (WQI) standards of water quality. Overall, the result showed that the DO, BOD, COD, and SS values were analysed within class II and III, while for NH3-N was analysed within class II, IV, and V under normal pH and temperature of water. The results also reported moderate levels for pollution between class I and IIA and the water in this area is safe for human consumption, but not suitable due to the significant presence of harmful microbes. Chitosan )Ch) and activated carbon (PAC), long known for its antibacterial activity and relatively low-cost, is an attractive potential biocidal agent. Characterization of Polyethersulfone (PES) Ultrafiltration (UF) membrane coated by an antimicrobial polymer chitosan and chitosan-PAC composite (Ch-PAC) at different concentration (chitosan: [ 2.0 % (w/v), 1.0% (w/v), 0.5% (w/v), 0.1% (w/v)], and chitosan-PAC composite: [1.5% (w/v) - 1.0 (w/v), 0.5 % (w/v) - 0.2% (w/v)] were examined under pH6. The chitosan coated-membrane led to the membrane has a higher water flux result (9.46×10-3) for Ch2 1.0% (w/v) and (8.053×10-3) for Ch3 0.5% (w/v) was decreased with increasing the concentration. Furthermore, the contact angle of the chitosan-coated membrane surface was dropped gradually from (78.80 for Ch1 2.0 % (w/v) to 51.20 for Ch4 0.1% (w/v)). The zeta potential of chitosan was (16.5 mV) and of PAC (-22.3 mV) predominates. In addition, membrane mechanical strength deteriorated as concentration increased but led to decreased mechanical properties of the membrane. Notwithstanding, It can be easily seen that the (Ch-PAC) coated membrane can perform more strongly than the (Ch) coated membrane. The swelling test shows that high chitosan concentration is more susceptible to hydrolysis than low chitosan concentration. Moreover, The biodegradation test results suggested that the number of bacteria with high biodegradability such as the chitosanase gene in soil is have got a close result with chitosan-degrading bacteria medium. As a result, the coated membrane exhibited significant antibacterial activity leading to (Ch 28% / Ch-PAC 45%) reduction in the number of attached live bacteria for total coliform bacteria in Anak Air Batu River and (Ch 45% / Ch-PAC 22%) reduction in the number of Varsity Lake samples. These results were verified by Extended Derjaguin–Landau–Verwey–Overbeek (XDLVO) model to determine the biofilm formation ability by isolated bacteria (Bacillus.Sp and E.Coli) on modified membranes. The three interaction energy components, the Van der Waals interaction energy (LW), electrostatic interaction energy (EL), and acid-base interaction energy (AB) were combined to evaluate the total membrane and bacteria interaction energies. Moreover, a high repulsion is found dominated by electrostatic energy even though LW energy is attractive. The bacterial adhesion has been observed on all samples within a short distance of (<5 h). Hence, this model confirms the less possibility of aggregation between the bacteria on coated membrane. However, aggregation may not be permanent due to long distance interactions caused by repulsive LW-AB components. Finally, all of the studied membrane were found to have substantially low surface energies compared to the bacteria and the interaction energies between the membranes and bacteria were predicted by the acid-base interaction energies of the bacteria. The flow cell and microscopic analysis of autoaggregation using 4, 6-Diamidino-2-Phenylindole (DAPI) staining showed a low level of interaction on the coated membrane as compared to normal PES membrane. These results indicated that the (Ch) and (Ch-PAC) composite coated PES membrane is a very promising membrane material used for water treatment in removing coliform bacteria and also prevent biofilm formation in water samples.